2017
DOI: 10.12659/msm.900515
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 10-Day Intensive Health Promotion Program Combining Diet and Physical Activity on Body Composition, Physical Fitness, and Blood Factors of Young Adults: A Randomized Pilot Study

Abstract: BackgroundA lifestyle characterized by poor eating habits and physical inactivity is a risk factor for multiple lifestyle diseases in young adults. This study assessed the effects of implementing an intensive 10-day health promotion program combining diet and physical activities on body composition, physical fitness, and biochemical parameters of young adults.Material/MethodsIn this randomized pilot study, 30 female undergraduate students were randomly allocated to an intervention and a control group. The heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
0
18
0
5
Order By: Relevance
“…However, the findings of another study indicated that moderate PA did not lead to a lower fat mass [33]. Moreover, Lee et al concluded that higher PAL leads to the development of muscle mass [34]. Similarly, in the study by Preto et al on nursing students, researchers found a positive association between PA and muscle mass [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings of another study indicated that moderate PA did not lead to a lower fat mass [33]. Moreover, Lee et al concluded that higher PAL leads to the development of muscle mass [34]. Similarly, in the study by Preto et al on nursing students, researchers found a positive association between PA and muscle mass [35].…”
Section: Discussionmentioning
confidence: 99%
“…Pada penelitian ini meskipun sudah diberikan konseling namun subjek masih sulit untuk mengontrol asupan makan karena wilayah kerja kantor yang dekat dengan restoran fast food dan lingkungan kantor yang kurang mendukung. Hasil penelitian lainnya berupa program promosi kesehatan intensif selama 10 hari dapat memperbaiki berat badan, IMT, kekuatan, fleksibilitas, keseimbangan dan kebugaran kardiorespiratori pada mahasiswa (22). Oleh karena itu, salah satu faktor keberhasilan pada program weight management pada pekerja adalah kondisi lingkungan kerja.…”
Section: Hasil Penelitianunclassified
“…S pregledom literature smo najpogosteje zaznali zdravstveni coaching kot pristop za hkratno obravnavo prehrane in telesne dejavnosti mladostnikov in mladih odraslih (Nguyen, et al, 2013;Svetkey, et al, 2015;Tucker & Lanningham-Foster, 2015;Allman-Farinelli, et al, 2016;Stephens, et al, 2017). To je pričakovano zaradi povezanosti obeh dejavnikov ter komplementarnega delovanja prehranskih navad in telesne dejavnosti na izgubo telesne mase (Lee, et al, 2017). Zaznali smo pomanjkanje raziskav o preprečevanju prekomernega uživanja alkohola in kajenja.…”
Section: Diskusijaunclassified